2011
DOI: 10.1007/s10147-010-0179-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous zoledronic acid and oral ibandronate on early changes in markers of bone turnover in patients with bone metastases from non-small cell lung cancer

Abstract: Considering the changes in bone markers, ZOL and oral IBA show comparable efficacy in patients with NSCLC and bone metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 37 publications
(36 reference statements)
2
49
0
Order By: Relevance
“…Currently, no comparative studies of bisphosphonates have been undertaken in prostate cancer, and ibandronate, pamidronate, and clodronate have not been directly compared in any malignancy. Indirect evidence suggests that zoledronic acid and ibandronate might be similarly active at reducing bone turnover markers in patients with breast and nonsmall cell lung cancer (18,19), whereas preclinical studies indicate that zoledronic acid is more than 16,000 times more potent than clodronate, 850 times more potent than pamidronate, and 20 times more potent than ibandronate (20).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, no comparative studies of bisphosphonates have been undertaken in prostate cancer, and ibandronate, pamidronate, and clodronate have not been directly compared in any malignancy. Indirect evidence suggests that zoledronic acid and ibandronate might be similarly active at reducing bone turnover markers in patients with breast and nonsmall cell lung cancer (18,19), whereas preclinical studies indicate that zoledronic acid is more than 16,000 times more potent than clodronate, 850 times more potent than pamidronate, and 20 times more potent than ibandronate (20).…”
Section: Introductionmentioning
confidence: 99%
“…At 3 months, s-CTX was reduced by 72.6% and 66.4% (p = 0.22), respectively. BALP levels were decreased similarly by both BPs at 1 month (ZOL 24.7%, and ibandronate 24.2%) and at 3 months (ZOL 28.6%, and ibandronate 24.2%) reporting an overall comparable efficacy [84].…”
Section: Biomarkersmentioning
confidence: 48%
“…Twelve studies (17 publications) met the inclusion criteria, including a total of 1,767 participants (Figure 1) [6, 7, 18, 25-39]. Of these, only seven studies reported sufficient data for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…None of the studies described the method of randomization (e.g., random number table) or allocation concealment (e.g., sealed envelopes). Only three trials described baseline similarity among the groups [25, 27, 36]. Blinding was often not feasible, especially when non-drug treatment modalities (e.g., radiation therapy) were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation